Od Sjedinjenih Američkih Država do Kine: Međunarodna razvojna pomoć kao instrument geopolitike / From the United States to China: International Development Assistance as an Instrument of Geopolitics (Pregled: časopis za društvena pitanja / Periodical for social issues, 2026)
International development aid is a means by which a certain country can implement its own geopolitical goals in a certain area. In the paper, we will try to present how international development aid has an effect in the geopolitical context, and we will examine what its main goals are. This type of activity is most often noticeable in large powers such as the United States of America and China, but it is evident that the countries of the European Union are also continuously investing their resources in this segment. In the context of the methodological approach, historical, polyeconomic, analysis, data collection2, compilation, and synthesis methods will prevail in this work. The main results we reached indicate that international development aid is a geopolitical tool of great powers, which can achieve the desired results, but not necessarily, which is our main hypothesis. The paper will present examples of how great powers use development aid for geopolitical purposes, from the end of the Second World War until today, and that this type of action is a globally widespread phenomenon.
Keywords: international development assistance; geopolitics; development; geopolitical instrument; China; United States; European Union